Thin endometrium restricts peri-ovulatory physiological transition between anti-adhesive and adhesive receptivity modulators - Celik, Onder; Ersahin, Aynur; Gungor, Nur D.; Ulug, Ulun; Celik, Nilufer; Yardim, Meltem; Akkoc, Ramazan F. (Elsevier Sci Ltd, 2025)
Research question: Does endometrial thinning affect the physiological transition of the endometrium from a non-receptive to a receptive state? Design: Fifty-eight women who underwent total embryo freezing were divided into three groups according to their endometrial thickness (EMT): group 1, EMT <= 7 mm; group 2, 7 mm < EMT <= 10 mm; and group 3, EMT > 10 mm. Group 1 was considered as having a thin EMT and groups 2 and 3 as a normal EMT. Endometrial sampling was performed at the time of oocyte retrieval. Anti-adhesive podocalyxin (PDX), adhesive homeobox A10 and A11 (HOXA10, HOXA11) and leukaemia inhibitory factor (LIF) mRNA, proinflammatory cytokines, oxidative stress markers and collagen deposition were determined. Results: Compared with groups 2 and 3, the relative expression of HOXA10, HOXA11 and LIF mRNA was down-regulated in group 1 (all P < 0.001), while PDX levels significantly increased (P < 0.001). The nuclear factor-kappa B, long pentraxin 3 (PTX3), tumour necrosis factor-alpha and total oxidant status of the thin endometrium group were significantly higher than those of participants with normal endometrium (all P < 0.001), while total antioxidant status was significantly lower (P < 0.001). The histoscore values for PTX3, PDX and Masson's trichrome were significantly higher in the thin endometrium group (P < 0.001 for each). Each millimetre increase in EMT decreased the risk of down-regulation of adhesive receptivity genes. The adjusted odds ratio for PDX was 1.69, representing a 69% increase in PDX expression. Conclusion: Endometrial thinning causes defective expression of anti-adhesive and adhesive receptivity modulators, restricting the transition of the endometrium from a non-receptive to a receptive state.
Keywords: Adhesive receptivity genes; Anti-adhesive protein; Collagen deposition; Endometrial thickness; Proinflammatory cytokines; Redox balance